The Impact of Mobile Phone Addiction on Education, Mental and Physical Health among University Students in Bangladesh - Kabir, Humayun; Sarker, Jiban; Islam, Md. Reazul (Eximia, 2023)
Mobile phone is a great invention of the modern science which was invented for making our life easy and comfortable, but it is not only confined into benediction side, rater it has turned into addiction and malediction as well. It has become a worldwide problem. The hitch is being so accelerated that the future of our next generation is under a massive threat. Day by day the problem is growing severe. The university students, the future of our nation as well as the ordinary people of the world are also no exception of the addiction. Therefore, this study aims to identify the prevalence and extent of mobile addiction among university students so that how long in a day they use mobile phone can be identified. Besides, the study tries to explore the factors contributing to mobile addiction among them, in consequence the positive and negative aspects towards their education, physical and mental health can be recognized. Apart from these, the study examines the impact of mobile addiction on the academic performance, mental and physical health of university students as well. For the study quantitative and qualitative components have been implemented where a cross-sectional survey design is ensured. The quantitative aspect involves conducting a survey among 12 university students (6 public and 6 private universities) in Bangladesh to investigate the current situation of mobile device addiction on educational studies and psychological sound health. The survey conducted through online .To ensures a diverse representation of participants from various faculties and academic levels, a stratified random sampling method has been utilized for participant selection. As a result, it has been found that it carries both positive and negative aspects. But most of the students are impacted negatively. Consequently they are going to lose a good career, a sound physical and mental health and better life.